RUSSIA IN THE CASPIAN - ZHILTSOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2004)
For centuries Russia has been the center of power in the Caspian; for centuries it has conducted an active policy there. Today, it can rely on its experience of multisided and bilateral cooperation in the region. In December 1991, however, it revealed to the world an image that dramatically differed from all previous historical forms of its statehood. This is true of Russia’s political system, its borders, and its geopolitical neighbors.1 Azerbaijan, Turkmenistan, and Kazakhstan joined Iran and Russia as in-dependent states. Their fuel reserves added weight to their international prestige. D. Yergin, one of the leading experts in oil-related issues, has said: “We should expect an ‘unexpected surprise,’ which will become obvious post factum. Everything that might affect our access to the sources of oil—violence, wars, technogenic threats, political collisions, economic imperatives, ethnic, religious, ideological, or social conflicts—could strike out of the blue.”2